Quick Calculation Ability on Students Metacognitive Using Wordwall Media in Class III Students at SDN Manukan Kulon Surabaya - Elsofi Alintya; Hery Setiyawan; Diyas Age Larasati (EduLine: Journal of Education and Learning Innovation, 2022)
Mathematics is a branch of science that has an important role in the development of science and technology. Students at the elementary school level have a lack of understanding of the material presented, causing learning outcomes to be not optimal and do not achieve complete learning. The purpose of this research is to measure the ability of quick calculation ability on students' metacognitive used wordwall media in class III students at SDN Manukan Kulon Surabaya. The research design used descriptive qualitative research methods. The subjects of this study were class III students taken with the Purposive Sampling Technique in accordance with the criteria set by the researcher. The results showed that the wordwall media can help students in working on metacognitive ability test questions effectively with a score range of 1642-504 and students are helped in working on test questions with the wordwall media. This is because there are 3 subjects that have categories of metacognitive levels of Reflective Use, Strategic Use and Aware Use.